Sexual Desire in Opiate-Dependent Men Receiving Methadone-Assisted Treatment - Yee, Anne; Loh, Huai Seng; Ng, Chong Guan; Sulaiman, Ahmad Hatim (SAGE Publications, 2018)
Low sexual desire (SD) is not life threatening, but its negative impact on the quality of life and intimacy of a relationship among the patients on methadone maintenance therapy (MMT) is significant. This cross-sectional study involved 183 men on MMT who were interviewed and who completed the Malay version of the SDI-2 (SDI-2-BM), the Malay version of the self-rated Montgomery–Asberg Depression Rating Scale (MADRS–BM) and World Health Organization Quality of Life–BREF Scale (WHOQOL–BREF) questionnaires. Findings showed 32.8% (n = 60) participants had low SD. Those who were older, had sexual partners, and were smokers achieved lower scores in both dyadic SD (≤24) and solitary SD (≤6), and suffered lower quality of life in their social relationship. MMT is very cost-effective in rehabilitating opioid dependence; however, as clinicians, we need to address and manage the issues of low SD and depression among patients on MMT, especially the older men.